1986
DOI: 10.1017/s0021859600087098
|View full text |Cite
|
Sign up to set email alerts
|

Growth of sugar-beet crops including the influence of synthetic plant growth regulators

Abstract: Observations are presented from a crop of sugar beet grown in Cambridgeshire during 1978, and a field trial at Sutton Bonington during 1985 in which the influence of synthetic plant growth regulators (PGRs) daminozide, chlormequat, GA 4+7 and ethephon were compared.Several distinct patterns of growth were evident, being similar for both growing seasons and described by two intersecting straight lines. Early development was characterized by a slow rate of biomass accumulation, a dominance of foliage production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…He identified two phases of constant allometry; an early phase which favoured leaf growth and a later phase dominated by storage-root growth. Green et al (1986) reached a similar conclusion; they also suggested that the transition from one phase to the next was induced by the onset of rapid division and expansion of cells within the secondary cambia of the root and that, perhaps, this was a response to shortening daylength.…”
Section: Dry-matter Partitioningmentioning
confidence: 76%
See 3 more Smart Citations
“…He identified two phases of constant allometry; an early phase which favoured leaf growth and a later phase dominated by storage-root growth. Green et al (1986) reached a similar conclusion; they also suggested that the transition from one phase to the next was induced by the onset of rapid division and expansion of cells within the secondary cambia of the root and that, perhaps, this was a response to shortening daylength.…”
Section: Dry-matter Partitioningmentioning
confidence: 76%
“…The relationships between the weights of root dry matter or sugar and total dry matter were examined in terms of the slopes and break-point of a two-phase linear regression model, as used by Green et al (1986). The model was fitted using the Maximum Likelihood Program (MLP; Ross, 1980) with weighting to equalize the variance within the wide data range.…”
Section: Mathematical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Terry (1968) stated that growth of the root slowly increases until about six weeks after emergence, and after that, the accumulation of dry matter in the root increases from the sum of the leaves and the petiole, thus developing separate stages for growth Leaf and root growth. Green et al (1986) stated that the transition from one stage to another may be due to the shortening of the day. On this basis, it is expected that the rapid root growth takes place in a short time period or at a certain stage of the plant growth period.…”
Section: Fig 5 Sugar Beet Root To Shoot Dry Matter Ratio During the mentioning
confidence: 99%